Banks' holdings of risky sovereign bonds in the absence of the nexus: Yield seeking with central bank funding or de-risking? - Rainer Frey; Mark Weth (Deutsche Bundesbank, 2019)
For the largest 55 German banks, we detect the presence of countercyclical yield seeking in the form of acquisition of high-yielding periphery bonds in the period from Q1 2008 to Q2 2011. This investment strategy is pursued by banks not subject to a bailout, banks characterised by high capitalisation, banks that rely on short-term wholesale funding, and trading banks. In the subsequent period up to 2014, these banks switched to a procyclical divestment strategy resulting in the sale of risky assets. Following the launch of the public sector purchase programme (PSPP) in 2015, a clear investment pattern can no longer be identified. Unlike existing evidence for banks domiciled in vulnerable countries, we find that the recourse to central bank finance is rather limited and does not affect the risk-taking behaviour of banks in the non-stressed country Germany. Yield-seeking strategies were predominantly pursued by healthy banks in Germany. This contrasts with the increases in domestic sovereign holdings in vulnerable countries which can be primarily regarded as the result of moral suasion or, for weakly capitalised banks, a kind of "indirect" moral suasion or "home-biased" gambling for resurrection.
Keywords: G11; G21; F34; H81; 330; sovereign-bank nexus; sovereign bond holdings; yield seeking; moral suasion; capital adequacy; expansionary monetary policy; home bias; Sovereign-bank nexus; sovereign bond holdings; yield seeking; moral suasion; capital adequacy; expansionary monetary policy; home bias